A new oral amoebicid (RO 7-0207) in the treatment of intestinal amoebiasis - S. H. Pudjiadi; Sunoto Sunoto; Suharjono Suharjono; Nartono Kadri (Indonesian Pediatric Society, 1973)
Amoebiasis is a widespread disease with the diffusion of the parasitevarying more with hygienic than geopraphic conditions. The incidencevaries from country to country. Soysa (1971) has estimated that ten per cent of the world-population suffers from amoebiasis. Udani et al. (1971) said that